Impacts of PU Foam Stand-Off Layer on the Vibration Damping Performance of Stand-Off Free Layer Damping Cantilever Beams. (17th November 2020) - Liang, Longqiang; Huang, Weibo; Lyu, Ping; Ma, Mingliang; Meng, Fandi; Sang, Yingjie
Abstract : Stand-off free layer damping is a vibration reduction method based on the traditional free layer damping. In this paper, a stand-off free layer damping cantilever beam is prepared with the steel plate as the base layer, rigid polyurethane (PU) foam as the stand-off layer, and rubber as the damping layer, and the motion equation of the cantilever beam is derived. The dynamic mechanical properties of damping rubber and PU foam are tested and analyzed. Through hammering tests, we have studied the effect of the density and thickness of the PU foam layer on the amplitude-frequency curves, modal frequencies, and loss factors of the cantilever beams. The results show that the rubber damping material is a major font of energy dissipation of the cantilever beam, and PU foam acts mainly to expand the deformation of the damping layer and plays a role in energy consumption. By increasing the density and thickness of PU foam within a certain range, the vibration peaks of the first five modes of the cantilever beam decreases gradually, the loss factors rise, and the damping performance is improved. Meanwhile, increased density and thickness enhances the overall stiffness of the beam, making the modal frequencies get higher.